What do our nurses know about managing patient with permanent pacemakers? - Ismail, Muhamad Al Muizz; Ibrahim, Nor Marini; Che Hasan, Muhammad Kamil (Faculty of Nursing Universitas Airlangga, 2020)
The number of patients with pacemaker implant is increasing in the health services sector in Malaysia, which requires nurses to have expertise in patient care with pacemaker implantation. Therefore, this study was conducted to analyse the level of knowledge among nurses regarding the management of patients with pacemaker implantation. Method: A cross-sectional study was conducted through purposive sampling among all nurses working at the critical care unit, intensive care unit, cardiac rehabilitation ward, investigation clinical laboratory, and non-invasive clinical laboratory in a public hospital in Kelantan. A questionnaire consisted of demographic data and nurses’ knowledge was distributed. Data were analysed for descriptive analysis and using Pearson correlation test. Result: Results from all respondents (n=70), show 48.6 % of the respondents had moderate knowledge about patient management with pacemaker implantation, 32.9 % had a low level of knowledge and only 13.6% had high knowledge regarding management of patient with pacemaker implantation. There is a significant difference between the level of knowledge and demographic data, that is between the level of education (p=0.027), age (p=0.011) and length of service (p=0.015). There is no significant relationship between knowledge and demographic data, such as gender (p=0.481), marital status (p=0.315), and post-basic (p=0.067). Conclusion: Level of knowledge among nurses about the management of patient with pacemaker implantation is low to moderate. Additional education and exposure among nurses are needed to enhance the knowledge of nurses and improve the quality of care among patients with pacemaker implant.